Analysis of Evolution, Expression and Genetic Transformation of TCP Transcription Factors in Blueberry Reveal That VcTCP18 Negatively Regulates the Release of Flower Bud Dormancy - Li, Yongqiang; An, Shuang; Cheng, Qiangqiang; Zong, Yu; Chen, Wenrong; Guo, Weidong; Zhang, Lu (Frontiers in Plant Science, 2021)
Plant-specific TEOSINTE BRANCHED 1, CYCLOIDEA, PROLIFERATING CELL FACTORS (TCP) transcription factors have versatile functions in plant growth, development and response to environmental stress. Despite blueberry’s value as an important fruit crop, the TCP gene family has not been systematically studied in this plant. The current study identified blueberry TCP genes (VcTCPs) using genomic data from the tetraploid blueberry variety ‘Draper’; a total of 62 genes were obtained. Using multiple sequence alignment, conserved motif, and gene structure analyses, family members were divided into two subfamilies, of which class II was further divided into two subclasses, CIN and TB1. Synteny analysis showed that genome-wide or segment-based replication played an important role in the expansion of the blueberry TCP gene family. The expression patterns of VcTCP genes during fruit development, flower bud dormancy release, hormone treatment, and tissue-specific expression were analyzed using RNA-seq and qRT-PCR. The results showed that the TB1 subclass members exhibited a certain level of expression in the shoot, leaf, and bud; these genes were not expressed during fruit development, but transcript levels decreased uniformly during the release of flower bud dormancy by low-temperature accumulation. The further transgenic experiments showed the overexpression of VcTCP18 in Arabidopsis significantly decreased the seed germination rate in contrast to the wild type. The bud dormancy phenomena as late-flowering, fewer rosettes and main branches were also observed in transgenic plants. Overall, this study provides the first insight into the evolution, expression, and function of VcTCP genes, including the discovery that VcTCP18 negatively regulated bud dormancy release in blueberry. The results will deepen our understanding of the function of TCPs in plant growth and development.